PENGARUH BRAND IMAGE CUSTOMER PERCEIVED VALUE CUSTOMER EXPERIENCE DAN BRAND TRUST TERHADAP LOYALITAS PASIEN PADA RUMAH SAKIT SANTO ANTONIO BATURAJA SUMATERA SELATAN - Saputra, Yakobus Angga Ricardo; Hidayat, Dasrun; Rubini, Rizki Adriansyah (LPPM Universitas Ibnu Sina, 2026)
Healthcare services have undergone rapid development due to advancements in technology, demographic changes, and increasing patient demands. To remain relevant and competitive, healthcare organizations must adapt to current trends and implement effective management strategies. This study aims to investigate the extent to which brand image, perceived value, customer experience, and brand trust influence patients' decisions to continue choosing Santo Antonio Baturaja Hospital. A quantitative method using multiple linear regression analysis was applied to data collected from 96 patient respondents. The results showed that all four variables simultaneously had a significant influence on patient loyalty (p < 0.001), with 84.3% of the variation in patient loyalty being explained by these variables. These findings indicate that a combination of these factors plays a crucial role in building long-term relationships with patients. Based on these results, it is recommended that the hospital continue to strengthen its brand image, improve service quality to provide a better patient experience, and focus on increasing perceived value and patient trust.